Uphill sprint vs. intermittent running in young soccer players: acute physiological responses - Ibba, G.; Pizzolato, F.; Di Michele, R.; Scorcu, M.; Attene, G.; Paradisis, G.; Anon, P.; Chamari, K.; Padulo, J. (Sport Sciences for Health, 2014)
Purpose: This study aimed to compare the acute effects of uphill repeated sprinting "with long recovery" (RS) and uphill intermittent running (IR) training on heart rate (HR) and blood lactate (BL) responses. Methods: Thirteen young male soccer players randomly performed in two separate occasions, on a slope (10 %), an RS and an IR session. RS consisted of three sets of eight maximal uphill 20-m sprints with long (90 s) recovery between sprints, and 8 min passive rest between sets, whereas IR consisted of 24 repetitions of 22-m sub-maximal (95 % of maximum speed achieved in an incremental test) uphill runs interspersed by a 15-s downhill walking recovery, lasting for a total duration of 8 min. Results: The mean HR, expressed as the percentage of HRMAX, was significantly higher in IR than in RS (86.1 ± 3.1 vs. 77.0 ± 4.5 %, respectively, p < 0.05). Conversely, BL measured after 3 min was significantly higher in RS (5.9 ± 1.1 mmol L-1) than in IR (2.9 ± 1.2 mmol L-1, p < 0.05). Conclusions: The differences found between RS and IR may be attributed to the different work/recovery ratios and speed characteristics. Therefore, uphill IR seems more suitable when the target is to tax the aerobic system, while RS may be more suitable when the focus is on stimulating the speed without increasing the metabolic demand.